Nutritional profile of olympic boxers and evaluation of the impact of nutritional intervention in weight adjustment to boxing categories - de Oliveira Nunes Perón, Alessandra Paula; da Silva Garcia, Luciana; Garcia Alvarez, Juan Francisco; Zampronha Filho, Waldir; da Silva, Alex Wilson (O Mundo da Saúde, 2009)
Fighting sports are generally divided into categories defined by weight bands, and this is a constant concern for athletes, who many times manipulate their body by using unsafe strategies mainly to reduce body weight. The aim of this work was to evaluate the impact of nutritional intervention in weight adjustment for each category of Olympic Box. The sample was composed by 10 athletes from the Brazilian Boxing Team in the period from January 2007 to February 2008. The strategies used for weight reduction and the anthropometric profile were investigated. Each athlete received a customized alimentary planning. All athletes answered that they used strategies for altering their weight. The main ones were: the use of clothes and gadgets that increase sweat production, liquid ingestion restrictions, fast and semi-fast. At the beginning, athletes presented an average 5,8kg above the weight of the category they were in. After three months of nutritional intervention this average fell to 4,4kg and in 6 months to 2,8kg. The average reduction of fat percentage was 6,3%, showing a positive impact of the used nutritional intervention. Due to the damages produced by fast weight loss procedures on health and performance, it is extremely important to know the anthropometric profile of athletes, preventing them to fight in categories not compatible anthropometric characteristics.